2020
DOI: 10.2106/jbjs.oa.20.00048
|View full text |Cite
|
Sign up to set email alerts
|

Anemia at Presentation Predicts Acute Mortality and Need for Readmission Following Geriatric Hip Fracture

Abstract: Background: There is a paucity of research regarding the relationship between anemia and postoperative morbidity and mortality among geriatric patients presenting with hip fracture. The objective of this study was to determine the effect of anemia at presentation on 30-day morbidity and mortality among geriatric patients with hip fracture. Methods: The American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database was queried for all hip fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 52 publications
1
21
0
3
Order By: Relevance
“…Multiple clinical parameters have been proposed as predictors for postoperative ADL recovery, including age, sex, surgical delay, preinjury status, [31][32][33] preoperative hemoglobin values, renal function, and handgrip strength [34,35]. In the present study, nine clinical variables were identified to be independently associated with postoperative BI in the GEE univariate analysis.…”
Section: Discussionmentioning
confidence: 73%
“…Multiple clinical parameters have been proposed as predictors for postoperative ADL recovery, including age, sex, surgical delay, preinjury status, [31][32][33] preoperative hemoglobin values, renal function, and handgrip strength [34,35]. In the present study, nine clinical variables were identified to be independently associated with postoperative BI in the GEE univariate analysis.…”
Section: Discussionmentioning
confidence: 73%
“…This study also observed an increased mortality associated with anemia. Finally, a large study investigated the association between anemia at presentation and postoperative mortality for elderly patients with a mean age of 79.2 years [167]. At presentation, 65% of these patients were anemic, and anemia was then associated with an increased odds ratio for mortality (1.3/p = 0.004); there was no significant association between anemia and myocardial infarction or cerebrovascular events.…”
Section: Increased Mortality Of Anemic Patients After Surgerymentioning
confidence: 99%
“…Anaemia progresses significantly during the days before surgery, more so in extracapsular fractures. In hip fracture patients, anaemia has been associated with increased risk of blood transfusion, poorer functional outcomes and increased mortality [ 102 ]. Hip fracture surgery is additionally associated with perioperative blood loss frequently requiring transfusion.…”
Section: Perioperative Carementioning
confidence: 99%